Students’ Responses to Brainstorming by Short Videos of Tourist Attractions in Writing Descriptive Text (A Case Study at the Eighth Grade of Junior High School) - Siti Wildan Diniati; Predari Siswayani; Dahlya Indra Nurwanti (ELITE Association Indonesia, 2021)
The success or failure of the teaching process depends on several elements, including the media employed by the teacher. This research intends to discover the process of brainstorming by short videos of tourist attractions in teaching writing descriptive text and students' responses to it. It concerns attaining students' responses after learning using the medium. This study uses a qualitative method with a case study. The data of responses were gathered from observation and interviews. A total of 17 students in the eighth grade of SMP Islam Nunuk and a teacher as participants in observation and six of them were interviewed using a semi-structured format. The findings showed that the process of brainstorm using the medium in teaching descriptive text using an observation checklist was successfully implemented. During the teaching-learning process, the students tend to become active participants. Then, all the responses from the six students with low, medium, and high levels favor the teacher to provide the medium to teach the descriptive text. Students can find an idea and have enough inspiration to write with feeling happy. From the results of the research, it can be summarized that using short videos for brainstorming in writing descriptive text got a positive response from students. Keywords: Brainstorming; Descriptive Text; Short videos of tourist attractions; Students’ response